The degree of application of electronic management in the schools of Al-Mujardah governorate and its relation to improving school performance - Al Shehri, Abdullah Moeid Abdullah (Journal of Educational and Psychological Sciences, 2018)
The study aimed to identify the degree of application of e-management in the schools of Al-Majarda governorate and its effect on improving the school performance from the point of view of teachers and teachers, and the effect of variables; years of experience, educational stage, gender; In order to achieve the objectives of the study, the analytical descriptive approach was followed. The questionnaire was used as a tool that was applied to a sample of 291 teachers and teachers of the various stages of education. In the statistical analysis of data (SPSS), the study reached the following results:- The e-management application has a medium average (3.57), and at the dimension level, after the electronic application reached the highest average (3.77). Followed by electronic monitoring and evaluation (3.57), electronic organization (3.53), and electronic planning (3.42), all of which are medium.- The performance of the teachers at the highest level (4.10) was followed by the performance of the administrative staff (3.97) and the performance of the school leader (3.93) and finally; Student performance (3.70) is all very high.- There were statistically significant differences at the level of (α = 0.05) according to the sex variable in the electronic planning dimension only, for the benefit of the parameters, and the absence of significant differences in the rest of the dimensions.- There were statistically significant differences at the level of (α = 0.05) according to the variable years of experience in all dimensions; and for the benefit of the category of less than five years.- There are statistically significant differences at the level of (α = 0.05); depending on the variable of the educational stage; between the responses of the sample groups on all dimensions of the axis of the degree of application of electronic administration, and for the class (middle stage).- The existence of a correlation relationship (medium); a statistical function at the level of significance (α = 0.05) between the aspects of the application of electronic management and the improvement of school performance.- In the light of the results, a number of recommendations and proposals for the implementation of e-administration were presented in schools.
Keywords: application; electronic management; schools; Al-Majardah Governorate; relationship; improving performance